Manometric perfusion test in biliary strictures treatment - Černa, Marie; Thomas, Rohit Philip; Köcher, Martin; Peregrin, Jan H; Válek, Vlastimil; Havlik, Roman; Froňkova, Sona; Kozák, Jiři; Panek, Jiři; Zaplatelova, Jana; Bilkova, Alena (Hepato-gastroenterology, 2012)
BACKGROUND/AIMS: To assess the biliary manometric perfusion test (BMPT) for evaluating success in treating benign biliary strictures. METHODOLOGY: During 2003 to 2010, 29 patients were subjected to BMPT after percutaneous balloon dilatation treatment. Intrabiliary pressure less than 20cm of water was considered the success threshold. Results of BMPT evaluation were retrospectively compared with a similar group where the standard clinical test was used for evaluating treatment success. The clinical test group included 21 patients treated for biliary strictures from 1994 to 2006. RESULTS: The two groups were statistically similar by age and gender. The BMPT group was tested without complications and pressure inside the biliary tree was less than 20cm of water in 27 of 29 patients. Subsequently, catheters were removed from all 27. Three patients required re-interventions 13 days, 11 months and 32 months later. Kaplan-Meier survival analysis showed that the probability of biliary patency at 3 year was 82.2%. There was no significant difference between groups by this measure (log rank test, p=0.624). CONCLUSIONS: The manometric test is an alternative for evaluating success in treating benign biliary strictures. It is simple, less time-consuming, economical, safe, effective and more comfortable for patients than the clinical test.
Keywords: Biliary Tract; dospělí; Kaplan-Meier Estimate; Recurrence; Female; manometrie; Adult; ženské pohlaví; Kaplanův-Meierův odhad; mladý dospělý; Cholangiography; lidé; tlak; katetrizace; Manometry; recidiva; Constriction, Pathologic; drenáž; cholangiografie; zaváděcí katétry; Contrast Media; Drainage; Middle Aged; Catheters, Indwelling; retrospektivní studie; Male; cholestáza; kontrastní látky; Aged; Young Adult; Catheterization; lidé středního věku; senioři; mužské pohlaví; Cholestasis; Retrospective Studies; stenóza; žlučové ústrojí; Pressure; Humans